Kontribusi Sektor-Sektor Utama Terhadap Produk Domestik Regional Bruto (PDRB) Kabupaten Balangan Tahun 2012-2021 - Rifa'ini, Ahmad; Rizali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study aims to determine how the contribution of the main sectors to the Gross Regional Domestic Product (GRDP) in Balangan Regency. The data used are secondary data, namely data on the Gross Regional Domestic Product (GRDP) of the mining sector, agricultural sector, trade sector and construction sector from 2012-2021, with the type of quantitative descriptive research collected through documentation techniques and literature studies. The data analysis technique used is contribution analysis. The results of this study show that the main sectors with the largest contribution to the GRDP of Balangan Regency are the mining sector, the agricultural sector, the trade sector and the construction sector.